2022
DOI: 10.1001/jama.2022.2929
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surfactant Therapy vs Sham Treatment and Death or Bronchopulmonary Dysplasia in Preterm Infants With Respiratory Distress Syndrome—Reply

Abstract: To the Editor The OPTIMIST-A trial 1 found that minimally invasive surfactant therapy, compared with sham treatment, did not reduce the incidence of the composite outcome of death or bronchopulmonary dysplasia in preterm infants with respiratory distress syndrome. However, the incidence of bronchopulmonary dysplasia was significantly lower in the minimally invasive surfactant therapy group (relative risk, 0.83; 95% CI, 0.70-0.98).In addition, although there was no significant difference in death between groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 7 publications
2
42
2
Order By: Relevance
“…The largest study (OPTIMIST) randomised 485 babies of 25–28 weeks with blinding of the intervention: LISA surfactant versus sham procedure at FiO 2 threshold 30%. Although there was no significant difference in the primary outcome of death or BPD, there was a significant reduction in BPD in survivors favouring the treated infants (37% vs. 45%) [73]. However, it is unclear if any differences can be attributed solely to the LISA method, as earlier compared to later surfactant in RDS is already known to be beneficial, and two-thirds of control infants received surfactant [73].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest study (OPTIMIST) randomised 485 babies of 25–28 weeks with blinding of the intervention: LISA surfactant versus sham procedure at FiO 2 threshold 30%. Although there was no significant difference in the primary outcome of death or BPD, there was a significant reduction in BPD in survivors favouring the treated infants (37% vs. 45%) [73]. However, it is unclear if any differences can be attributed solely to the LISA method, as earlier compared to later surfactant in RDS is already known to be beneficial, and two-thirds of control infants received surfactant [73].…”
Section: Introductionmentioning
confidence: 99%
“…Although there was no significant difference in the primary outcome of death or BPD, there was a significant reduction in BPD in survivors favouring the treated infants (37% vs. 45%) [73]. However, it is unclear if any differences can be attributed solely to the LISA method, as earlier compared to later surfactant in RDS is already known to be beneficial, and two-thirds of control infants received surfactant [73]. The LISA technique has been widely adapted in many parts of Europe and in large cohort studies there are better clinical outcomes [74].…”
Section: Introductionmentioning
confidence: 99%
“…1,6 In light of these observations, more stringent BPD definitions based on a systematic assessment of the need for respiratory therapy using pulse oximetry became more widely used in more recent randomized clinical trials (RCTs) to improve the consistency of the diagnosis of BPD across neonatal units. [14][15][16][17] Two large RCTs 18,19 that were specifically designed to determine the effect of high-dose enteral DHA supplementation during the neonatal period on BPD outcomes in preterm infants who were born before 29 weeks' gestation used such a systematic physiological BPD definition at 36 weeks' PMA. Contrary to the aforementioned hypothesis, both trials reported an overall increase of BPD with the use of DHA but an inconsistent association with BPD-free survival in analysis by gestational age (GA) and mode of delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In the Reply Letter titled “Minimally Invasive Surfactant Therapy vs Sham Treatment and Death or Bronchopulmonary Dysplasia in Preterm Infants With Respiratory Distress Syndrome—Reply,” published in the April 26, 2022, issue of JAMA , a sentence was incorrectly worded. In the second to last paragraph, the last sentence should have been “Beyond the surfactant received as part of the minimally invasive surfactant therapy intervention, in both groups any other surfactant therapy given followed accepted guidelines in relation to dosage, timing, and F io 2 threshold.” This article was corrected online.…”
mentioning
confidence: 99%